SEJARAH TRADISI UPACARA GHATIB BEGHANYUT DI KECAMATAN MEMPURA KABUPATEN SIAK - ', Nurkhasanah; ', Isjoni; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Siak is one of the districts located in Riau Province and has a lot ofculture and Islamic tradition since the Sultanate of Siak is still maintained. One of themin the village Mempura an area that was once the center of a great Malay kingdom ofthe Kingdom of Siak with culture and Islamic tradition is tradition Ghatib Beghanyut ,starting reinforcements ritual performed Siak community for generations. BeghanyutGhatib this tradition is an annual tradition or is only done once a year in every monthof Safar . Named Ghatib Beghanyut as an activity of remembrance , tahlil and prayerthat is done on the ferry and boat for the purpose of land fame , prosperity , peace andavoid all the plagues that will befall the public with an infectious disease such asmeasles , diarrhea and other diseases. The aim of research to find out the history of thetradition Ghatib Beghanyut in District Mempura Siak , to know the process ofimplementation of the tradition Ghatib Beghanyut in District Mempura Siak Regency ,to determine the function of tradition Ghatib Beghanyut in District Mempura SiakRegency , to determine the change in the tradition Ghatib Beghanyut in KecamatnMempura Siak , to determine the factors Siak community in conducting the ceremonytradition Ghatib Beghanyut in District Mempura Siak. In this research usingqualitative research methods . Qualitative method is a method that does not usenumbers in data collection and in providing interpretation of the results. In thisqualitative study using a descriptive approach. The results of research in general thatthe authors wrote beghanyut ghatib tradition is a tradition of local and communitystarting reinforcements in Siak . Beghanyut Ghatib ceremonies are carried outdepending on the condition how many signs the accident occurred , but in adults is doneonce a year precisely in safar.Keywords : Ghatib Beghanyut , Reject Bala , Safar , Siak , Mempura2